Significant reduction of peripheral blood interleukin-35 and CD4+EBI3+ T cells, which are negatively correlated with an increase in the plasma IL-17 and cTnI level, in viral myocarditis patients - Han Ouyang; Li Xiang; Jianchang Chen; Weiting Xu; Yang Jiao; Huaying Shen (Central European Journal of Immunology)
Introduction: Viral myocarditis (VMC) has become an increasingly common heart disease that endangers human health. In the present study, the plasma interleukin-35 (IL-35) level and the percentage of CD4 + EBI3 + T cells in VMC patients were detected to investigate the significance of changes in these parameters in the plasma of VMC patients and their association with the disease. Material and methods: ELISA was performed to detect the plasma IL-35 level and the percentage of peripheral blood CD4 + EBI3 + T cells in 40 VMC patients and in 20 healthy individuals. Moreover, the plasma IL-17 levels in the VMC patients and in the healthy individuals were detected using an ELISA, and the cardiac Troponin-I (cTnI) levels were detected using a chemiluminescent microparticle immunoassay to compare the differences in the groups. Results : Plasma IL-35 level and the percentage of CD4 + EBI3 + T cells in acute phase VMC patients was lower than that in the healthy control group and the convalescent phase VMC patients. Additionally, the plasma IL-35 level in the VMC patients exhibited a negative correlation with the levels of cTnI and IL-17. The percentage of CD4 + EBI3 + T cells also showed a negative correlation with the levels of cTnI and IL-17. Conclusions : The plasma IL-35 level and the percentage of CD4 + EBI3 + T cells in VMC patients was reduced, and the amount of the decrease was associated with the severity of the disease. These results suggest that IL-35 and CD4 + EBI3 + T might play important roles in the progression of VMC and could be used as indictors of the disease.